Holocene atmospheric iodine evolution over the North Atlantic - Corella J. P.; Maffezzoli N.; Alberto Cuevas C.; Vallelonga P.; Spolaor A.; Cozzi G.; Muller J.; Vinther B.; Barbante C.; Astrid Kjaer H.; Edwards R.; Saiz-Lopez A. (Climate of the Past, 2019)
Atmospheric iodine chemistry has a large influence on the oxidizing capacity and associated radiative impacts in the troposphere. However, information on the evolution of past atmospheric iodine levels is restricted to the industrial period while its long-term natural variability remains unknown. The current levels of iodine in the atmosphere are controlled by anthropogenic ozone deposition to the ocean surface. Here, using high-resolution geochemical measurements from coastal eastern Greenland ReCAP (REnland ice CAP project) ice core, we report the first record of atmospheric iodine variability in the North Atlantic during the Holocene (i.e., the last 11 700 years). Surprisingly, our results reveal that the highest iodine concentrations in the record were found during the Holocene Thermal Maximum (HTM; ∼ 11 500-5500 years before-present). These high iodine levels could be driven by marine primary productivity resulting in an Early Holocene "biological iodine explosion". The high and stable iodine levels during this past warm period are a useful observational constraint on projections of future changes in Arctic atmospheric composition and climate resulting from global warming.